Electrophoretic behavior of some shales from the setap formation, Sarawak Basin, Malaysia - Fosu-Duah, E.L. (Research India Publications, 2016)
Electrophoretic mobility has been used to investigate the surface potential characteristics of six shale samples from the Setap Formation of the Sarawak basin-Malaysia. The zeta potential ranged between +80 and -80 mV. Apart from one sample that remained electronegative throughout the entire pH range of this investigation, all the samples exhibited isoelectric points (IEP). The four of the IEP values were in the acidic range (2.4-3.62) which is characteristic of kaolinite rich colloids. The relatively high IEP of 7.92 reported by one of the samples was attributed to the shift by the mineral oxidic minerals (goethite) toward higher values. Further data analysis done outside the scope of the objectives of this study revealed a positive correlation between Fe2O3 and IEP with correlation coefficient of 0.82. This supports well-published relationships between the two parameters. The behaviour of the surface potential properties in the Setap Formation is an indication of variabilities in its sorption capacities. Â© Research India Publications.